Association of Autoimmune Thyroiditis and Type 1 Diabetes Mellitus With Severity of Children with Celiac Disease - Bashar S Khalaf (Indian Journal of Forensic Medicine & Toxicology, 2020)
Purposes of study: analysis and measurement of incidence and association between autoimmune thyroiditis(AIT) and type 1 Diabetes mellitus(T1DM) with clinical and serological severity of patients with Celiac disease.Design and Methods: This is prospective study, All children (107 children with 41 male and 66 female ) with celiac disease are admitted and follow up in Hospital. Age groups ( 1-12 years) are arranged into two groups (1-6 and 7-12 years old). The celiac disease are divided into: Group1= 25-50 IU/ml, Group2 = 50-100 IU/ml, Group3 >100 IU/ml. All patients with celiac disease are follow up for AIT and type 1 T1DM.Results: (107) patients with celiac disease, mean age is 6.78±2.85, median age is 8, and female :male ratio are 1.6:1. All celiac patients are divided into: group 1 (43 patients), group 2 (50 patients), and group 3 (14 patients). Incidence of T1DM in all patients is 8.4% while AIT 2.8% . T1DM incidence in group 2 is 3.7% and in group 3 is 12.3%. But AIT incidence in group 3 is 4.6%. All cases with AIT have hypothyroidism with TSH > 100 ?U/ml. All diabetic patients have random blood sugar > 450 mg/dl. Age group are divided into two groups, 1-6 and 7-12 years old. Incidence of T1DM are 6.25% and 11.6% in these two age groups respectively, while AIT is 7% in age group 7-12 years. The association between celiac patients groups with T1DM and AIT is insignificant association ( (P value is 0.265 and 0.717 respectively). Also age groups have no significant association with T1DM and AIT ( (P value is 0.48 and 0.062 respectively) .Conclusion: follow up of celiac disease is important step for diagnosis AIT and T1DM . These two autoimmune diseases are increasing especially when there high concentration of IgA anti-tissue transglutaminase level ( >100 IU/ml) and advanced children age group . AIT may presented initially with hypothyroidism.